Mesoporous Bamboo Biochar from Microwave-assisted Template/Hydrothermal Treatment for Adsorption of Organics - Yin Li; Xinyi Yu; Junfeng Zhang; Zengkun Wang; Tao Zhang; Jian Yang; Jun Dong; Shuqi Li; Chuang Xing; Xikun Gai (BioResources, 2025)
Recycling of residual biomass in the form of carbonaceous materials is a sustainable and economically viable management option with zero net carbon dioxide emissions. Mesoporous bamboo biochars were produced via microwave-assisted hydrothermal/soft template treatment. Then they were characterized and evaluated for their adsorption capabilities for three organics. The biochars were found to have mesoporous structures with BET surface areas of 13.0 to 288 m2/g, total pore volumes in the range of 0.017 to 0.313 cm3/g, and average pore diameters between 4.0 and 6.7 nm in size. The surface areas and pore volumes were highly related to the hydrothermal treatment conditions. The mesoporous bamboo biochars showed adsorption amounts for 2-naphthol, berberine hydrocholoride, and Congo red in the range of 35.0 to 155.7, 76.1 to 129.6, 57.9 to 114.4 mg/g, respectively, at the adsorbate concentration of 0.5 mg/mL, and their adsorption capabilities depended on both the porosity and the surface groups. The adsorption of the three organics on the selected sample was a spontaneous and exothermic process with physical adsorption as the dominant mechanism. The adsorption could achieve equilibrium within 20, 40, and 60 min for 2-naphthol, berberine hydrochloride, and Congo red, respectively. This study provides a prospective method to produce biomass-derived mesoporous carbon adsorbents for adsorptive separation of organics from water.